Analisa Penggunaan Video Game sebagai Media Dakwah - Arditya Prayogi (IAIN Padangsidimpuan, 2021)
The development of da'wah today is very rapid. This rapid development is also supported through various media, including popular culture media (Pop Culture). Of the many popular cultures, video games are rarely used in da'wah media because they are often considered as trivial things, not of important value, and also considered as wasteful/consumptive activities. In fact, video games are suspected to be able to shape changes in the mindset and behavior of the players. This study uses a qualitative approach through analysis of literature obtained from books, journals and other relevant sources. This study aims to examine conceptually and practically the use of video games as a medium of da'wah that can open up opportunities to disseminate messages of da'wah massively and significantly. The results show that the phenomenon of using video games as a popular propaganda medium can theoretically be examined in three perspectives, namely video games as a way of delivering/intervention to change behavior through the learning process, video games as a simulation and a model that presents a meaningful experience, and video games as part of an environment that is able to provide various (direct) activities that are useful and meaningful from the learning aspect. Practically, the use of video games as a medium of Islamic da'wah can be realized in three ways, namely building the entire process of developing a video game platform by involving Muslim components in it. Then by inserting Islamic elements, and involving other platforms outside the video game system.